Optimization of Pectinase Enzyme Liquefaction of Banana ‘Gros Michel’ for Banana Syrup Production - Sukuntaros Tadakittisarn; Vichai Haruthaithanasan; Penkwan Chompreeda; Thongchai Suwonsichon (Agriculture and Natural Resources, 2007)
The pectinase enzyme liquefaction of banana ‘Gros Micheal’ pulp was optimized by response surface methodology (RSM). The effect of pectinase enzyme concentrations (0-0.2%) and incubation times (60-300 min) on juice yield (%), total soluble solids (TSS), recovery soluble solids (RSS), clarity (%T670) and browning index (A420) of juice were studied using central composite design of experiments. Results showed that pectinase enzyme concentration played an important role that significantly (p ≤ 0.001) influenced most of dependent variables of banana juice. The coefficient of determination (R2) of yield (%), recovery soluble solids (RSS), clarity (%T670) and browning index (A420) were 0.907, 0.924, 0.804 and 0.793, respectively. The optimum condition for enzymatic extraction was 0.15% of pectinase enzyme incubated for 120 min at 50°C. The yield was ≥ 62%, RSS ≥14, %T670 ≥ 96% and A420 ≤ 0.1. The physicochemical compositions of syrup were mostly three times higher than juice owing to the concentration that increased from 24 to 74° Brix except for pH, clarity (%T670), CIE L* which were not changed.